PENDIDIKAN ISLAM DI SPANYOL DAN SISILIA - Firdaus Firdaus (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The entry of Islam in Spain in 711-1492 (781 years) and in Sicily from 827-1194 AD (367 years) is inseparable from the expansion of the territory proclaimed by the Umayyad caliph through the North African pathway which made both regions world-famous both in the field of education and civilization. The pattern of Islamic education held in these two regions basically consists of two levels, namely Kuttab who studied basic and intermediate knowledge. Spain was then regarded as an unrivaled center of Islamic culture and science after Constantinople and Baghdad So it was no wonder then that other European nations began coming to this Andalusian country to study the sciences of the Spanish Muslims by studying fruits books of Andalusian scholars either clandestinely or openly. Sicily that once ruled Islam from the year 881 AD to 1091 M. As in Toledo Andalusia, the city of Palermo is an important place for translation activities of Islamic scholars into Latin.